PENYULUHAN DAN LATIHAN FISIOTERAPI UNTUK MENCEGAH NYERI PUNGGUNG PADA PEKERJA KANTORAN - Yunita, Alfitri Yana; Nurshal, Rezki Amalia; Mutiara, Sherly (LPPM Universitas Awal Bros, 2025)
Back pain is one of the most common musculoskeletal disorders faced by office workers, primarily caused by poor ergonomic posture and prolonged sitting. This community service project aimed to enhance the knowledge and skills of office workers in preventing back pain through counseling and simple physiotherapy exercises. The intervention included interactive lectures, demonstrations of stretching and muscle-strengthening exercises, and Q&A sessions. Results showed a significant improvement in participants' understanding of proper posture and their ability to perform exercises independently. Following the program, 85% of participants reported feeling more comfortable during work, and 65% experienced a reduction in back pain. The program was well-received and is expected to help reduce the incidence of back pain, improve productivity, and promote a healthy workplace culture. The company also expressed interest in incorporating these practices into regular employee training. This project highlights the importance of ergonomic education and physical activity in preventing musculoskeletal disorders and improving employee well-being in the workplace.